(untitled) (Palíndromo, 2017)
The article approaches a set of five installations of the artist Armanda Duarte. This reflection explores how the artist contrasts the ephemeral character of the works and the frailty of their materials with a geometric or mathematical rigor. The operations of measurement and displacement articulated at these artworks, as well as the the floor as a space for presentation, are issues addressed in this text, highlighting the vulnerability of this place and the adhesion to a reversible and open montage. The article places the belonging of Armanda Duarte´s installations to a private collection in deposit in the Serralves Museum of Contemporary Art, Portugal and their different exhibitions.